THE INFLUENCE OF ORGANIZATIONAL CULTURE, SELF EFFICACY AND WORK MOTIVATION FOR EMPLOYEE PERFORMANCE - Hendra Wiyanto; C. Catur Widayati; Siti Marliya (Dinasti International Journal of Education Management And Social Science, 2022)
This research aims to find out the influence of organizational culture, self efficacy and work motivation on employee performance. Telecommunications in Jakarta using a quantitative descriptive approach. In this study, the population used as many as 60 employees who are permanent employees of PT Telecommunications. This study sample technique uses saturated sampling with a sample of as many as 60 employees. The data collection method used in the study used questionnaires. Data analysis in this study uses an alternative method of structural equation modeling (SEM) namely partial least square (PLS). This research proves that organizational culture has a positive and significant effect on employee performance, self efficacy has a positive and significant effect on employee performance and work motivation has a positive and significant effect on employee performance.